Effects of in-play cooling during simulated tennis match play in the heat on performance, physiological and perceptual measures - Wiewelhove, T.; Conradt, F.; Rawlins, S.; Deacon, J.; Meyer, T.; Kellmann, M.; Pfeiffer, M.; Ferrauti, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this crossover study was to investigate whether a cooling intervention during simulated tennis match play in the heat could affect players` performance, physiology, perception of effort, and well-being. METHODS: Eight competitive male tennis players performed two testing sessions of 45-minute simulated tennis match play on a hard court at 31.8±2.1°C and 48.5±9.6% relative humidity. During change-of-end breaks, the cooling interventions (COL) consisted of cold-water ingestion (ad libitum) and an electric fan facing the players at a distance of 1 m combined with an ice-filled damp towel around the neck and on the thighs or no cooling (CON) were applied. Measures of performance, heart rate, blood lactate concentration, tympanic and local skin temperature, sweat loss, perceived exertion, and thermal sensation as well as ratings of recovery were recorded in both sessions. RESULTS: Paired-samples t-tests showed no significant differences (P>0.05) in any of the measures between COL and CON. Effect size (ES) calculations indicated moderate evidence that COL was beneficial to local skin temperature (ES=-0.95) and thermal sensation (ES=-0.77). At the individual level, a positive response to COL was found in some players for heart rate, local skin temperature, thermal sensation, and ratings of recovery. CONCLUSIONS: A likely inability of COL to improve players` performance or reduce thermal strain during tennis match play in hot humid conditions was found at the group level. However, some players may be more likely to benefit from COL. Therefore, the use of COL should be individualized.